A kryptoracemic salt: 2-{[2,8-bis(triﬂuoromethyl)quinolin-4yl](hydroxy)methyl}piperidin-1-ium (+)-3,3,3-triﬂuoro-2-methoxy-2-phenylpropanoate - Wardell, James L.; Wardell, Solange M. S. V.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The asymmetric unit of the title salt, C17H17F6N2O+·C10H8F3O3-, comprises two piperidin-1-ium cations and two carboxylate anions. The cations, each having an L-shaped conformation owing to the near orthogonal relationship between the quinolinyl and piperidin-1-ium residues, are pseudo-enantiomeric. The anions have the same absolute configuration but differ in the relative orientations of the carboxylate, methoxy and benzene groups. Arguably, the most prominent difference between the anions occurs about the Cq-Om bond as seen in the Cc-Cq-Om-Cm torsion angles of -176.1 (3) and -67.1 (4)°, respectively (q = quaternary, m = methoxy and c = carboxylate). The presence of Oh-H...Oc and Np-H...Oc hydrogen bonds leads to the formation of a supramolecular chain along the a axis (h = hydroxy and p = piperidin-1-ium); weak intramolecular Np-H...Oh hydrogen bonds are also noted. Chains are connected into a three-dimensional architecture by C-H...F interactions. Based on a literature survey, related molecules/cations adopt a uniform conformation in the solid state based on the letter L.